Case Report: Emergency mitral valve plasty in an unstable dog with left atrial rupture secondary to myxomatous mitral valve disease - Wada, Tomoki; Takemura, Ryosuke; Yotsuida, Hideki; Ohashi, Misato; Miyashita, Naoki; Uezawa, On; Mori, Takuya (Frontiers in Veterinary Science, 2026)
ObjectiveTo describe the medical and surgical management of recurrent left atrial rupture (LAR) in a dog with severe mitral regurgitation (MR). This report focuses on challenges encountered with pericardiocentesis, the role of hemodynamic support, and the importance of invasive blood pressure monitoring.Case summaryAn 11-year-old, weighing 2.9 kg, male Chihuahua was scheduled for mitral valve plasty due to severe MR. The dog developed acute collapse and dyspnea and was diagnosed with LAR and pulmonary edema; pericardiocentesis was withheld due to relatively stable hemodynamics. Despite inotropic support and diuretics administration, a second LAR occurred the following day during transport for echocardiographic examination, with a large intrapericardial clot preventing pericardiocentesis and causing shock. Although fluid therapy and ephedrine administration improved blood pressure, invasive blood pressure monitoring and strict rest were subsequently employed to maintain a lower systolic pressure, enabling safe anesthetic induction. Under cardiopulmonary bypass, clot removal was performed. Intraoperatively, due to inadequate venous return, the heart enlarged and a third LAR occurred, necessitating repair of the rupture site with a pericardial patch under cardioplegic arrest alongside chordae tendineae reconstruction. Postoperatively, the dog developed dyspnea potentially related to lung injury, transfusion effects, or residual pulmonary edema, which resolved with medical management. Marked thrombocytopenia emerged soon after switching antibiotics but improved rapidly following corticosteroid administration and discontinuation of the suspected antibiotic. The dog was discharged in good condition and remained clinically stable 1 year later.ConclusionThis case provides a detailed account for the stepwise medical and anesthetic management of recurrent LAR secondary to severe MR. During conservative treatment, pericardiocentesis was not always effective, particularly in the presence of intrapericardial clots, which might have interfered with drainage. In the setting of cardiac tamponade, increasing pre- and after-load along with positive inotropic support appeared to contribute to temporary hemodynamic stabilization. Invasive arterial pressure monitoring allowed for stable hemodynamic control and safe anesthetic induction, underscoring its importance for preoperative management. Furthermore, the third intraoperative rupture was successfully repaired using a pericardial patch, which achieved effective hemostasis and demonstrated its potential value as a surgical option for LAR repair.